Climate Change and Observed Climate Trends in the Fort Cobb Experimental Watershed. Issue 4 (1st July 2014) - Garbrecht, J. D.; Zhang, X. C.; Steiner, J. L.
Abstract : Recurring droughts in the Southern Great Plains of the United States are stressing the landscape, increasing uncertainty and risk in agricultural production, and impeding optimal agronomic management of crop, pasture, and grazing systems. The distinct possibility that the severity of recent droughts may be related to a greenhouse‐gas induced climate change introduces new challenges for water resources managers because the intensification of droughts could represent a permanent feature of the future climate. Climate records of the Fort Cobb watershed in central Oklahoma were analyzed to determine if recent decade‐long trends in precipitation and air temperature were consistent with climate change projections for central Oklahoma. The historical precipitation record did not reveal any compelling evidence that the recent 20‐yr‐long decline in precipitation was related to climate change. Also, precipitation projections by global circulation models (GCMs) displayed a flat pattern through the end of the 21st century. Neither observed nor projected precipitation displayed a multidecadal monotonic rising or declining trend consistent with an ongoing warming climate. The recent trend in observed annual precipitation was probably a decade‐scale variation not directly related to the warming climate. On the other hand, the observed monotonic warming trend of 0.34°C decade −1 that started around 1978 is consistent with GCM projections of increasing temperature for central Oklahoma.